Traditional Herb Used and Training on Preparation Moringa oleifera Lam. Herb as Dip and Capsules - Yufri Aldi; Salman Umar; Aditya Alqamal Alianta; Elidahanum Husni (Warta Pengabdian Andalas, 2024)
Moringa leaves have grown abundantly in the 50 Kota Regency area. Studies have been carried out regarding moringa leaves, and research has shown that moringa leaves are effective as a medicine to increase the body's immunity. The community needs to know and understand the benefits of Moringa leaves. Based on that circumstance, the Community Service regarding how to process the Moringa leave to be dip preparation and capsule has been conducted in Jorong Padang Kandis, VII Koto Talago Sub-district, Guguk District, 50 Kota Regency, West Sumatra. The activity was carried out on 19 August 2023. The participants were the Family Welfare Movement (PKK) and Bundo Kandung groups in Jorong Padang Kandis, attended by 100 participants. The method was lectures and training on preparing Moringa herb leaf preparations and making Moringa leaf capsules, which the community can use directly. Community services topics were "The Utilisation of Traditional Medicines" and "The Efficacy and Research Results of Moringa Leaves." The training was on making Moringa leaf powder based on suitable traditional medicine-making methods, such as dips and capsules from Moringa leaf powder and extract. Community service helped the community understand that Moringa leaves can be used as a traditional medicine to protect the body from infection with microorganisms. The community also made powder packaged as a dip preparation, used like tea bags and put it into capsules.